In vitro study of in silico designed sirtuin 1 and bromodomain 4 inhibitors on human neuroblastoma SH-SY5Y and acute myeloid leukemia U937 cells - Stander, Barend Andre (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.